Hibernoma-like Changes and TFE3 Expression in Mesothelioma Mimicking TFE3-Translocation Renal Cell Carcinoma: A Diagnostic Pitfall. (September 2021) - Hoton, Delphine; Luyckx, Mathieu; Galant, Christine; Dano, Hélène
The long delay between asbestos exposure and the development of mesothelioma will likely result in an increased incidence of mesothelioma in our industrialized societies. Radiation therapy is another factor known to induce these tumors. We describe a rare case of foamy looking mesothelioma in a 63-year-old patient with a long oncology history of a supposed peritoneal carcinomatosis. The pathologist was faced with a diagnostic pitfall as this peritoneal clear cell tumor expressed transcription factor binding to immunoglobulin heavy constant mu enhancer 3 (TFE3) at the nuclear level. Fortunately, the pathologist performed an extensive panel of immunomarkers, leading to a final diagnosis of epithelioid mesothelioma. Thus, we describe the first case of mesothelioma expressing TFE3. Note that there was no rearrangement of TFE3 in fluorescence in situ hybridization.